Do literacy and numeracy pay off? On the relationship between basic skills and earnings - Manfred Antoni; Guido Heineck (Institute for the Study of Labor (IZA), 2012)
Is there a reward for basic skills in the German labor market? To answer this question, we examine the relationship between literacy, numeracy and monthly gross earnings of full-time employed workers. We use data from the ALWA survey, augmented by test scores on basic cognitive skills as well as administrative earnings data. Our results indicate that earnings are positively related to both types of skills. There furthermore is no evidence for non-linearity in this relationship and only little heterogeneity when differentiating by sub-groups.
Keywords: I21; J31; 330; literacy; numeracy; earnings; administrative data; Germany; ALWA; Analphabetismus; Mathematik; Bildungsniveau; Lohn; Schätzung; Bildungsertrag; Deutschland